Convolution Algorithm for Numerical Reconstruction of Digitally Recorded Holograms with Extended Field of View - Trujillo, C.; Serna, S.; Monroy, F.; Garcia-Sucerquia, J. (Photonics Letters of Poland, 2010)
In this letter, the range of application of the convolution approach to numerical reconstruction of digitally recorded holograms is extended. By numerical manipulation of the digitally recorded hologram, the convolution approach is used for reconstructing digital holograms of objects larger than the recording device. Experimental results are shown to validate the proposed method. Full text: PDF References: E. Cuche, P. Marquet, and Ch. Depeursinge, "Spatial Filtering for Zero-Order and Twin-Image Elimination in Digital Off-Axis Holography", Appl. Opt. 39(23), 4070 (2000). [CrossRef] M. Born, E. Wolf, Principles of Optics (Cambridge University Press, seventh (expanded) edition, 1999). J.W. Goodman, Introduction to Fourier Optics (The McGraw-Hill Companies Inc, second Edition, Printed in Singapore, International Editions, 1996). L.P. Yaroslavsky, F. Zhang and I. Yamaguchi, "Algorithm for reconstruction of digital holograms with adjustable magnification", Opt. Lett. 29(14), 1668 (2004). [CrossRef] F. Monroy, O. Rincón, Y. Torres, J. Garcia-Sucerquia, "Quantitative assessment of lateral resolution improvement in digital holography", Opt. Commun. 281, 3454 (2008). [CrossRef] E. Cuche, P. Marquet and Ch. Depeursinge, "Simultaneous amplitude-contrast and quantitative phase-contrast microscopy by numerical reconstruction of Fresnel off-axis holograms", Appl. Opt. 38(34), 6994 (1999). [CrossRef]